The use of variable temperature 13 C solid-state MAS NMR and GIPAW DFT calculations to explore the dynamics of diethylcarbamazine citrate - Venâncio, Tiago (Magnetic resonance in chemistry : MRC, 2019)
© 2018 John Wiley & Sons, Ltd.